A psicologia jurídica em intersecção com o direito penal: das práticas diagnósticas às práticas restaurativas - Caldas, Rafaela de Sousa (2019)
The present research discusses the urge of some psychologic practices in the Brazilian criminal law field from the foucaultian genealogy perspective. The analysis proposed by Foucault, in order to denaturalize practices, objects and speeches, enables a historical and combative point of view that seeks to map the different strategies that provoke the emergency of events. Through this historical reading, it was intended to map the ruptures that the Brazilian Justice, in reference to different kinds of practices and ways of understanding about the crime and penalty in the criminal law field, given that these ruptures culminate in the emergence and transformation of different psychologic practices in this field. From normative and institutional files, three main ruptures that composed the analysis of this research were found, which are: the foundation of the 1940’s Penal Code and the proposal of individualization of penalties, which culminated in the urge of the evaluation and diagnostic practices in psychology; the creation of special criminal courts and the proposal of alternative penalties instead of prision, that focused on a resocializing perspective of the punishment, with the emergence of psychologic practices of monitoring and inspection of these resolutions; and, for last, the urge of consensual methods of conflict resolution, adopting multiple penal practices, guided by the restauration of relations and for the promotion of a peace culture, culminating in a pluralism of law practices, with the insertion of different personages and agents in the criminal law. The path that was build has made it possible to localize the relations between different socio- political knowledges, practices and interests, regarding to different strategies of action against the crime, being the creation and expansion of psychologic practices an interesting and powerful tactical resource adopted by the Brazilian criminal law through the years.